Determining the Shear Resistance in Landslides with Respect to Shear Displacement and Shearing Time in Drainage-Controlled Ring Shear Tests - Sueng-Won Jeong (Applied Sciences, 2022)
Shear stress is an important parameter in estimating the slope stability and flow dynamics in mass movements. The ring shear test can often be employed to determine the residual shear stress because of its suitability for large deformations for assumed in situ stress and drainage conditions. Determination of the residual shear stress of weathered landslide materials composed of coarse-grained sediments was examined with respect to the shear displacement and drainage condition. Based on the experimental results, the shear stress of landslide materials has typical maximum and minimum values (i.e., peak and residual shear stress). The measured shear stress generally increases with an increase in shear speed regardless of drainage condition. In general, the residual shear stress can be measured when a relatively long shearing time is applied. The residual shear stress, which is known as the minimum shear resistance at the initiation of landslide occurrence along the pre-existing slip surface of the landslide body, is also measurable even though limited shear displacement (0.1–100 mm) and shear speed (0.1–100 mm/s) are applied. The minimum range of residual shear stress of weathered soils obtained from the ring shear tests is roughly half of the value obtained from the direct shear tests. The residual shear stress can be used to estimate the reactivation of slope movement.